The Business of People : Leadership for the Changing World. - Fraser, Iain, 1955-; Taylor, Madeleine (Milton : Taylor & Francis Group, 2019)
The Business of People is purposefully focused on people. The book will assist you to develop and support yourself with your people leadership, knowledge, and skills. It is an opportunity to better manage yourself and lead others, including your organization, into the modern volatile, uncertain, complex, and ambiguous (VUCA) world. It is also a sequel to the top-selling book The Business of Portfolio Management: Boosting Organizational Value. Authors Madeleine Taylor and Iain Fraser combine to give you the very best in knowledge and experience in a variety of situations. This is a book that cuts through the nonsense and presents real-world solutions for situations facing leaders today and tomorrow. Shifting from managing people to leading people requires a pivot ... Leadership matters because the future is at greater risk without it. Regardless of where you are in your leadership journey I am confident this new book from Madeleine and Iain will be a valuable resource for you. Enjoy the journey, it never ends. --Mark A. Langley, Former President and CEO, Project Management Institute Iain and Madeleine are honest and raw about the challenges faced, and the resiliency needed, to lead in business. --Suzanne M. O'Gorman, Senior Strategic Business Architect, United Healthcare Group In a world where leadership increasingly requires emotional and cultural intelligence skills, this masterpiece couldn't be any timelier. --Dr. Hilary Aza, Senior Portfolio Manager, Tarrant County, Texas Essential for anyone seeking to better understand their personal leadership and to inform further development. --Rob Loader, Executive, Capital Planning & Delivery, Telstra Corporation The book to me is written from a position of empowerment, cultural acknowledgment, hopefulness, and purpose. --Elissa Farrow, Founder, About Your Transition This book will challenge your own thinking and behaviour and give you an opportunity to develop your adaptability and leadership style for an evolving future. --Thomas Davis, GM, Corporate Services, Capital & Coast District Health Board, New Zealand
OCLC-licensed vendor bibliographic record.
Keywords: Educational leadership; Listening; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Project Management; COMPUTERS -- Information Technology